2013
DOI: 10.2147/ijwh.s49843
|View full text |Cite
|
Sign up to set email alerts
|

Ethical aspects of obstetric care: expectations and experiences of patients in South East Nigeria

Abstract: BackgroundMedical ethics is not given due priority in obstetric care in many developing countries, and the extent to which patients value compliance with ethical precepts is largely unexplored.ObjectiveTo describe the expectations and experiences of obstetric patients in South East Nigeria with respect to how medical ethics principles were adhered to during their care.MethodsThis was a cross-sectional, questionnaire-based study involving parturient women followed in three tertiary hospitals in South East Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…We arrived at 6 main conceptual clusters, namely: Disrespect and Abuse/ Mistreatment during facility-based childbirth (D&A/ MISC) [ 27 56 ], Respectful maternity care (RMC) [ 57 63 ], Obstetric violence (OV) [ 64 70 ], Person-centered care (PCC) [ 71 75 ], Childbirth experiences (CE) [ 76 82 ], Maternal satisfaction (MS) [ 83 98 ]. We grouped concepts that were marginally used in a separate cluster named “Other” [ 99 107 ]. The results are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We arrived at 6 main conceptual clusters, namely: Disrespect and Abuse/ Mistreatment during facility-based childbirth (D&A/ MISC) [ 27 56 ], Respectful maternity care (RMC) [ 57 63 ], Obstetric violence (OV) [ 64 70 ], Person-centered care (PCC) [ 71 75 ], Childbirth experiences (CE) [ 76 82 ], Maternal satisfaction (MS) [ 83 98 ]. We grouped concepts that were marginally used in a separate cluster named “Other” [ 99 107 ]. The results are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Education and training are crucial for workforce efficiency. In Nigeria, the educational system is evolving slowly, and there is uncertainty about the direction it should take, particularly in fields such as medical ethics (Iyoke et al, 2013;Adeleke et al, 2019). However, studies have indicated that Rational Emotive Behavior Therapy (REBT) approaches have been efficient for improving Nigerian employees' general mental well-being and job relationships (Ede et al, 2021).…”
Section: Workforce Efficiencymentioning
confidence: 99%